Adoptive transfusion of tolerogenic dendritic cells prolongs the survival of liver allograft: a systematic review. Issue 2 (May 2014) - Xia, Meng Juan; Shan, Juan; Li, You Ping; Zhou, Yan Ni; Guo, Ying Jia; Sun, Gui Xiang; Wu, Wen Qiao; Feng, Li
Abstract Objectives To systematically review the effects of tolerogenic dendritic cells (Tol‐DCs) induced by different methods on liver transplantation and their possible mechanisms of action. Methods PubMed and EMbase were searched for relevant articles through 31 December 2013. The effects of Tol‐DCs on liver allograft survival were semiquantitatively evaluated, and the possible mechanisms by which Tol‐DCs prolong graft survival were analyzed. Results Seven articles were included, and classified according to methods of induction, sources, and methods of infusing Tol‐DCs. Tol‐DCs induced from immature DCs (imDCs), with cytokines, and by gene modification induced liver transplant tolerance for 33.1 ± 32.5 days (2.7‐fold vs. control), 26.17 ± 16.20 days (1.8‐fold vs. control), and 11.7 ± 1.6 days (2.3‐fold vs. control), respectively. DCs derived from recipient bone marrow, donor bone marrow, and donor spleen induced liver transplant tolerance for 51.0 ± 0.0 days (5.9‐fold vs. control), 21.4 ± 26.8 days (2.4‐fold vs. control), and 15.0 ± 0.0 days (2.3‐fold vs. control), respectively. The primary mechanisms by which Tol‐DCs induce liver transplant tolerance were the induction of T‐cell hyporeactivity and Th2 differentiation. Conclusions Tol‐DCs induced by three different methods could extend liver allograft survival, with imDCs showing optimal results. The optimal infusion method was intravenous injection of 1–2 × 106 Tol‐DC, similar to findings in renal transplantation. Tol‐DCs prolonged liver transplant tolerance more than renal transplant tolerance.